Treatment of community-acquired pneumonia in hospitalised patients - DURMUŞOĞLU, LÜTFİYE (Elsevier, 2001)
Community-acquired pneumonia (CAP) can be life-threatening. The prognosis is generally poorest in elderly patients and/or those with underlying chronic conditions, but fatalities can occur in all age groups. Current challenges in the clinical management of CAP are discussed, and the criteria for identifying those patients who should be treated in hospital with initial intravenous therapy are considered. Rapid initiation of therapy is important, using an agent that provides coverage against the most likely pathogens - Streptococcus pneumoniae and the atypical organisms. There is an increasing tendency to minimise the duration of intravenous therapy, with an early transition to oral therapy and the rapid return of the patient to the community. The efficacy of oral macrolides in the treatment of CAP is well established. Evidence for the use of intravenous azithromycin to provide effective and well-tolerated, first-line intervention in the hospitalized CAP patient is summarised. © 2001 Elsevier Science B.V. and International Society of Chemotherapy. All rights reserved.
Keywords: Azithromycin; Community-acquired pneumonia; Hospitalization; Intravenous therapy